2020
DOI: 10.1177/1178638819899398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a 3-Month Anti-inflammatory Dietary Intervention Focusing on Watermelon on Body Habitus, Inflammation, and Metabolic Markers: A Pilot Study

Abstract: An anti-inflammatory dietary intervention called the Inflammation Management Intervention (IMAGINE) was adapted to emphasize watermelon due to its anti-inflammatory properties. This pilot study (n = 23) tested the effect of a watermelon-enhanced IMAGINE intervention (n = 15) on body habitus and markers of inflammation and metabolism. This 3-month self-selection trial, consisting of weekly in-person classes and online education for 12 weeks, focused on incorporating watermelon into an already anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…One-third of all participants had an average diet with pro-inflammatory potential, which was significantly reduced by the change in diet quality, which was mainly due to reduced energy and macronutrient intake, and the significant increase in intake of nutrients with anti-inflammatory potential. Most studies that have used the change in DII ® as a tool to assess the inflammatory potential of a diet were observational or retrospective, and till now, there is limited evidence from intervention trials to support the claim that a reduction in DII ® scores through dietary changes leads to improvements regarding inflammation or related health risk factors [ 61 , 62 , 63 , 64 ]. The change in the anti-inflammatory potential of the diet in the AID group toward higher anti-inflammatory potential was somewhat smaller compared to similar studies [ 63 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…One-third of all participants had an average diet with pro-inflammatory potential, which was significantly reduced by the change in diet quality, which was mainly due to reduced energy and macronutrient intake, and the significant increase in intake of nutrients with anti-inflammatory potential. Most studies that have used the change in DII ® as a tool to assess the inflammatory potential of a diet were observational or retrospective, and till now, there is limited evidence from intervention trials to support the claim that a reduction in DII ® scores through dietary changes leads to improvements regarding inflammation or related health risk factors [ 61 , 62 , 63 , 64 ]. The change in the anti-inflammatory potential of the diet in the AID group toward higher anti-inflammatory potential was somewhat smaller compared to similar studies [ 63 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the present study, the following data were used: sex (female and male); self-reported colour/race (black, pardo or mixed, white, yellow, indigenous and unsure); age categorised in age range (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and above 60 years old); level of education evaluated in years of study (<9 years and ≥9 years) and income by monthly household income quartile.…”
Section: Socio-economic and Demographic Datamentioning
confidence: 99%
“…It is known that certain factors, such as economic and demographic aspects, can influence food choices. Especially in poor countries, studies have shown that individuals with higher levels of education and income consume more inflammatory diets, with higher values of DII (8,11,12) due to greater and easy access to foods rich in trans and saturated fat and added sugars. However, in affluent countries, the opposite pattern is observed, that is, more affluent people select diets with higher concentrations of phytochemicals, which tend to be strongly anti-inflammatory.…”
mentioning
confidence: 99%
“…could be presented one after the other or concurrently. If participants have a low mean score on familiarity then combining ingredients, including spices, creatively can add novelty while reducing the inflammatory potential of foods [ 10 ]. Although the FCQ and other surveys have been used in group and community settings in the past (as with the examples mentioned above), this is a novel suggestion for how these research tools should be employed in dietary interventions.…”
Section: Previous and Potential Future Uses Of Food Motives And Values Assessmentsmentioning
confidence: 99%
“…While dietary counselling or interventions range in duration from weeks to months, it make take years to establish and then maintain dietary changes [ 10 , 11 , 12 , 13 , 14 ]. Despite their potential to improve health, efforts aimed at dietary change are limited in important respects [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introduction: Challenges and Opportunities In Dietary Changementioning
confidence: 99%